Теоретические и экспериментальные исследования теплообменных процессов в пластинчатом испарителе - Кошельник, Вадим Михайлович; Фокин, Виталий Сергеевич; Кошельник, Александр Вадимович; Збараз, Леонид Иосифович (НТУ "ХПИ", 2011)
Lamellar heat exchangers with enlarged channel width are suggested to use as evaporators for thermal technological schemes. The results of theoretical and experimental investigations of heat exchange during boiling in vertical channels are presented. The new criterial dependences for calculation of heat exchange intensity are proposed.
Keywords: вертикальный канал; повышение энергоэффективности; пластинчатые теплообменники; кратность циркуляции; проходное сечение; паровой пузырь